Short-term Impact of Beach Fest on the Topography, Vegetation Coverage and Sediment Distribution of the Mengabang Telipot Beach, Terengganu - Husain, Mohd Lokman; Ismail, Khairul A'mali; Yaakob, Rosnan (Universiti Putra Malaysia Press, 1995)
Grid measurements of beach vegetation, beach profile surveys and sediment analyses were done before and after the beach fest in order to assess the impact of the festivities on a stretch of the Mengabang Telipot beach. Although the beach fest was held for only seven days, its impact on the beach was found to be damaging. Beach vegetation was completely destroyed, while the backshore and the front portion of the upper beach were eroded. Sediments on both the backshore and upper beach decreased in. mean size and became poorly sorted. The foreshore area, which was influenced by tides, was not affected by the beach festivities.